ESTETIKA HINDU PADA PEMENTASAN TOPENG SIDAKARYA DALAM UPACARA DEWA YADNYA - Ni Wayan Juli Artiningsih (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Aesthetics is essentially a way of looking at a sense of beauty (lango) that is bound by Hindu religious values based on the teachings of the holy scriptures. One of the realization of the teachings of Hinduism in Bali is realized with the implementation of Yadnya ceremony. In Hinduism it is known as Panca Yadnya, namely five kinds of sacred sacrifices offered to Deities, Rsi, Humans, Ancestors, and Butha (lower realms), known as Deva Yadnya, Rsi Yadnya, Pitra Yadnya, Manusa Yadnya, and Butha Yadnya. The emergence of Panca Yad itself is based on human existence which is covered by Rna (debt) which has been carried out since humans were born. The form of the yadnya carried out was outlined in the order of Ceremony and Upakara presented. In the implementation of the Yadnya Dewa ceremony, it was not only poured into an offering in the form of Upakara but was also followed by an art performance in the form of Sidakarya's Mask. This is based on the existence of the Sidakarya Mask which enters the bebali art level, where the existence of the Sidakarya Mask which functions as an accompanist from a Yadnya ceremony procession. Problems at this writing include; 1) What is the form of the Sidakarya Mask performance, 2) what is the Sidakarya Mask Function in the Yadnya Dewa Ceremony, 3) What is the Hindu aesthetic (tattva, ethics, ceremony) in the Sidakarya Mask performance. The conclusion is the form of staging which consists of stories, characterizations, venues, ceremonial facilities and accompaniment accompaniment, the function of the Sidakarya Mask performance is a religious function, a spiritual function and an educational function, while Hindu aesthetics are seen from the three aspects of values contained in the staging of the Sidakarya Mask at the ceremony Dewa Yadnya is the value of Tattva, Ethics, and Ceremony